2017
DOI: 10.1111/jomf.12393
|View full text |Cite
|
Sign up to set email alerts
|

Relatives in Residence: Relatedness of Household Members Drives Schooling Differentials in Mozambique

Abstract: Children typically receive investments from their fathers, but absent fathers often invest at low levels. In fathers’ absence, what types of non-fathers invest heavily in children? This paper investigates educational participation as a reflection of childhood investments on Ibo Island, Mozambique, where only one third of school-aged children live with their biological fathers. Father-present children generally attended school at the highest rates. Stepchildren and father-absent relatives (e.g. grandchildren, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Male extended kin and family exchange networks also assisted in adolescent utilization of formal health services, especially among boys. Similar to recent findings for the schooling of father‐absent children in Mozambique (Lopus, ), we found evidence that among boys living in female‐headed households, strong family exchange networks may have had a substitution effect for the absence of a male senior senior male in the household. For households with very low network scores (two standard deviations below the mean), boys in female‐headed households were at a particularly large disadvantage.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Male extended kin and family exchange networks also assisted in adolescent utilization of formal health services, especially among boys. Similar to recent findings for the schooling of father‐absent children in Mozambique (Lopus, ), we found evidence that among boys living in female‐headed households, strong family exchange networks may have had a substitution effect for the absence of a male senior senior male in the household. For households with very low network scores (two standard deviations below the mean), boys in female‐headed households were at a particularly large disadvantage.…”
Section: Discussionsupporting
confidence: 88%
“…Reflecting growing scholarly interest in family networks (Clark et al, , ; Lopus, ; Ruiz‐Casares, ; Tsai & Dzorgbo, ), we found that exchange networks and extended kin also played a role in adolescent health‐seeking behavior. In urban areas, male and female relatives were important sources of advice to youth regarding health problems, and they were especially important in accompanying youth to get treatment.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Multiple studies in northern Tanzania have found that fostered children are not disadvantaged in terms of mortality, anthropometric scores, or educational investment compared to biological children (Urassa et al 1997;Burke and Beegle 2004;Lawson et al 2017). In Mozambique, fostered children were not less likely to attend school than biological children within the same household (Lopus 2017). These studies suggest that fostering children need not always come at the cost of a child's well-being.…”
Section: Introductionmentioning
confidence: 94%
“…Various other claims about the abuse of stepchildren have been reported informally in SSA (Bowman and Brundige 2014), but without a clear quantitative analysis. One exception is the study by Lopus (2017) that used census data collected in 2009 and 2012 on Ibo Island in Mozambique to investigate educational participation as a reflection of childhood investments. The study assessed whether or not Mozambican children in all types of father-absent households received comparable educational investments, or if relatedness to children through blood or marriage dictated the level of investment in children's schooling.…”
Section: Introductionmentioning
confidence: 99%